Experimental study on properties of natural soils treated with cement kiln dust. (June 2019) - Rimal, Siddhartha; Poudel, Ram Krishna; Gautam, Dipendra
Abstract: Soil improvement by the addition of chemical or cementitious additives is emerged as a remarkable solution to provide a suitable ground for infrastructure construction. Previous studies have used several additives together with the cement kiln dust (CKD) worldwide. Using CKD as an additive would also lower the solid waste problem in cement industry, thus CKD can be used effectively as a sustainable solution. To illustrate the efficacy of CKD in soil improvement, this study treated two natural soils with several proportions of CKD for various curing periods. Extensive laboratory tests were carried out to depict the variation of unconfined compressive strength by treating the natural soils with CKD at various proportion. Samples were prepared for natural soils with and without CKD. Similarly, tests were carried out in dry and immersed conditions. The sum of results highlights that significant increment in the unconfined compressive strength is achieved when CKD is used as an additive in natural soil.